Vedānta and Psychological Well-Being: Spiritual Insights for Modern Life - Mishra, Koushik (Journal of Research in Innovative Teaching and Inclusive Learning, 2025)
Vedānta, one of the most influential philosophical traditions of India, provides profound insights into the nature of consciousness, human identity, and the ultimate reality of existence. Although Vedānta is often studied primarily as a metaphysical system, its teachings also offer valuable guidance for psychological well-being and mental health. In an era marked by rapid social change, technological advancement, and increasing psychological stress, individuals are searching for deeper sources of meaning and inner stability. This research article explores the relationship between Vedāntic philosophy and psychological well-being, focusing on key concepts such as self-realization, detachment, mindfulness, inner peace, and the transformation of consciousness. Drawing upon classical Vedāntic texts including the Upaniṣads, the Bhagavad Gītā, and the Brahma Sūtras, as well as interpretations by modern thinkers such as Swami Vivekananda and Sarvepalli Radhakrishnan, the study examines how Vedānta offers a holistic approach to mental health. The article also considers the relevance of Vedāntic insights for contemporary psychology, particularly in relation to stress management, emotional regulation, and the cultivation of resilience. It argues that the Vedāntic understanding of the unity of consciousness and the transcendence of ego-centered identity provides a powerful framework for achieving psychological balance and inner harmony. Ultimately, the study concludes that Vedānta can contribute significantly to modern discussions on psychological well-being by integrating spiritual wisdom with practical approaches to mental health.